2022
DOI: 10.3390/jimaging8040104
|View full text |Cite
|
Sign up to set email alerts
|

Explainable Multimedia Feature Fusion for Medical Applications

Abstract: Due to the exponential growth of medical information in the form of, e.g., text, images, Electrocardiograms (ECGs), X-ray, multimedia, etc., the management of a patient’s data has become a huge challenge. Particularly, the extraction of features from various different formats and their representation in a homogeneous way are areas of particular interest in medical applications. Multimedia Information Retrieval (MMIR) frameworks, like the Generic Multimedia Analysis Framework (GMAF), can contribute to solving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The extracted features are contributed to the MMFG, which can be further processed. Extensions of MMFGs have led to semantic analysis, such as Semantic Multimedia Feature Graphs (SMMFGs) and Explainable SMMFGs (ESMMFGs) [24]. Despite these extensions, the graph-based structure of MMFGs remains and can lead to slow processing times.…”
Section: Multimedia Features and Multimedia Feature Graphsmentioning
confidence: 99%
See 2 more Smart Citations
“…The extracted features are contributed to the MMFG, which can be further processed. Extensions of MMFGs have led to semantic analysis, such as Semantic Multimedia Feature Graphs (SMMFGs) and Explainable SMMFGs (ESMMFGs) [24]. Despite these extensions, the graph-based structure of MMFGs remains and can lead to slow processing times.…”
Section: Multimedia Features and Multimedia Feature Graphsmentioning
confidence: 99%
“…With the introduction of semantics to the MMFGs in [24], we introduced additional metrics to improve the efficiency and effectiveness of Graph Codes for MMIR. First, the feature discrimination M DIS is defined as the difference in the number of nonzero Graph Code fields for two feature vocabulary terms of a given Graph Code or Semantic Graph Code.…”
Section: Graph Codes and Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…"Smart MMIR" thus describes expressive, scalable, interoperable, explainable and human understandable MMIR solutions. In previous work [2][3][4], we already introduced, defined, and evaluated the core components, which contribute to Smart MMIR. However, the interoperability of these components and a corresponding formal model is a foundation for further improvements in the problem areas, which were mentioned above.…”
mentioning
confidence: 99%
“…In [3], we further showed that not only feature graphs, but also the indexing structures, such as, for example, graph codes, can be automatically transformed into humanunderstandable texts. Based on this, further metrics for semantic graph codes were introduced [4] as follows:…”
mentioning
confidence: 99%